2019
DOI: 10.1177/0885328219849368
|View full text |Cite
|
Sign up to set email alerts
|

In vivo endothelialization and neointimal hyperplasia assessment after angioplasty of sheep carotid artery with a novel polycarbonate polyurethane patch

Abstract: The aim of this study was to compare two variants of a novel polycarbonate polyurethane prosthesis with polyethylene terephthalate (Dacron) prosthesis in an established sheep model of carotid patch angioplasty. Two variants of the polycarbonate polyurethane prosthesis were used: (1) Polycarbonate polyurethane equal (PCU-e) prosthesis consisted of a multilayered porous structure with equal internal and external layers; (2) Polycarbonate polyurethane with more porous inner layers (PCU-mp) prosthesis had more por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Responses to the artificial blood vessels, and the quality and velocity of endothelialization could be different between human and sheep. 16 In our study, the length of implanted artificial blood vessels is about 2 cm, which cannot well reflect the clinical application scenarios. Besides, since this experiment is the first step of this preclinical animal experiment, it is mainly to verify the hemocompatibility, histocompatibility, effectiveness, and safety of this artificial blood vessel, so there are no control groups.…”
Section: Limitations Of the Studymentioning
confidence: 86%
See 3 more Smart Citations
“…Responses to the artificial blood vessels, and the quality and velocity of endothelialization could be different between human and sheep. 16 In our study, the length of implanted artificial blood vessels is about 2 cm, which cannot well reflect the clinical application scenarios. Besides, since this experiment is the first step of this preclinical animal experiment, it is mainly to verify the hemocompatibility, histocompatibility, effectiveness, and safety of this artificial blood vessel, so there are no control groups.…”
Section: Limitations Of the Studymentioning
confidence: 86%
“…Dacron) and polytetrafluoroethylene (PTFE). 16 However, the results of long-term follow up about Dacron V R grafts had demonstrated that the mismatch of biomechanical properties could cause multiple complications. 17 Hence, polyurethane (PU) artificial blood vessels were designed to reduce this mismatch between artificial blood vessels and innate arteries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, these studies did not clarify the difference between PC and DC after CEA. In addition, re-endothelialization on the patch has always been particularly concerning, as it is directly related to thrombosis (20). Moreover, it is also unclear whether the neointima on the patch is functional.…”
Section: Introductionmentioning
confidence: 99%